Female Sufi Authority: Sufi Ideas in Żikr an-Niswah al-Muta‘abbidāt aṣ-Ṣūfiyyāt by as-Sulamī - Muhammad Ihza Fazrian; Riyanto, Waryani Fajar (Universitas Islam Negeri Raden Mas Said Surakarta, 2025)
The ideas of Sufism actually do not recognize the identity of its followers, male or female. Women in Sufism have an important position so that their ideas need to be explored. One of the efforts to find the ideas of female Sufis is through Sufi hagiographic texts (ṭabaqāt). This research discusses the formation of the authority of female Sufis based on their ideas through one of the classic Sufi hagiographic texts by as-Sulamī. This type of research is qualitative, based on document research, and uses the analytical-descriptive method. The primary source is a female Sufi hagiography text by as-Sulamī entitled Żikr an-Niswah al-Muta'abbidāt as-Ṣūfiyyāt. Secondary sources are other classical Sufi hagiography texts such as those by al-Iṣfahānī, al-Harawī, al-Qusyairī, al-Hujwīrī, al-Jāmī, Ibn al-Jauzī, and 'Aṭṭār, as a well as supporting authoritative books and articles. The findings of this study show that, in addition to recognizing the existence of female Sufis, as-Sulamī managed to record their various statements that are full of Sufism ideas and this showed their authority in this tradition. The author collects their Sufism ideas in two main ideas; Tazkiyyah an-Nafs and Sufistic Ethics. The idea of Tazkiyyah an-Nafs is contained in their narratives which envision that humans can establish a positive relationship between themselves and their God. Meanwhile, the idea of Sufistic Ethics is contained in their narratives which discourse that the positive relationship between humans and their God, must form a similar thing between themselves and His creatures.